The "General Apostasy from Good Taste and Good Sense": Alexander Campbells Critique of Fashionable Religion - Groover, R. Edwin (Stone-Campbell journal, 1999)
Alexander Campbell often wrote about what the church ought to be ashe reacted to fashionable religion as he perceived it. While he becamesomewhat less iconoclastic as the years passed, he continued to promotethe repudiation of many aspects of fashionable religion in his day. Hecalled for simplicity in church buildings, furnishings, apparel, andmanners. It is against this backdrop that Campbell wrote disparagingly(though infrequently) about the use of instrumental music inworship services.